Health care worker vaccination against Ebola: Vaccine acceptance and employment duration in Sierra Leone. Issue 8 (14th February 2019) - Jendrossek, Mario; Edmunds, W. John; Rohan, Hana; Clifford, Samuel; Mooney, Thomas A.; Eggo, Rosalind M.
Abstract: Health care workers (HCW) are at high risk of Ebola virus disease (EVD) infection during epidemics and may contribute to onward transmission, and therefore HCW-targeted prophylactic vaccination strategies are being considered as interventions. To assess the feasibility of preventive HCW vaccination, we conducted a pilot survey on staff turnover and vaccine acceptance amongst 305 HCW in Freetown and Kambia districts of Sierra Leone. Multivariable logistic regression demonstrated which demographic and behavioural factors were associated with acceptance of a hypothetical new vaccine. We quantified the duration of employment of HCW, and used multivariable gamma regression to detect associations with duration of employment in current or any health care position. Finally, we simulated populations of HCW, to determine the likely future immunisation coverage amongst HCW based on our estimates of vaccine acceptance and employment duration. Most HCW we surveyed had a positive opinion of EVD vaccination (76.3%). We found that being a volunteer HCW (vs being on the government payroll) was associated with increased vaccine acceptance. We found that HCW have stable employment, with a mean duration of employment in the health sector of 10.9 years (median 8.0 years). Older age and being on the government payroll (vs volunteer HCW) were associated with a longer duration of employment in the health sector. Assuming a single vaccine campaign, with 76.3% vaccine acceptance, 100% vaccine efficacy and no waning of vaccine-induced protection, immunisation coverage was sustained over 50% until 6 years after a vaccination campaign. If vaccine-induced immunity wanes at 10% per year, then the immunisation coverage among HCW would fall below 50% after 3 years. Vaccinating HCW against EVD could be feasible as employment appeared stable and vaccine acceptance high. However, even with high vaccine efficacy and long-lasting immunity, repeated campaigns or vaccination at employment start may be necessary to maintain high coverage.